Literary Routes: Contributions to Natural/Cultural Heritage Tourism. How landscape transforms literature and tourism - Ruiz Scarfuto, Rosalinda (Campus di Rimini - Alma Mater Studiorum - Università di Bologna, 2013)
Literary routes inspired by landscapes is a topic where cultural and natural routes merge to form an added value of heritage that is greater than either one standing alone. Landscape is traditionally defined as a consequence of transformations by humans, and its scope rarely takes into account how nature has inspired literature to advance the “intellectual development of humankind,” hence transforming heritage. Literary routes paralleling transhumance routes embraced by the Sami, First Nations, or Spanish shepherds (full of landscapes, seascapes, and riverscapes), can actively transmit traditional technologies, biodiversity, and cosmic philosophy for the betterment of humankind; for example, the depth of literary heritage inspired by landscapes enhances our collective memory through a network of archives (libraries, collections). The continuous dissemination of this literature traversing borders, language barriers, and time periods has stimulated literary routes to emerge as a function of moving the experience from an intangible heritage based on imaginary landscapes to a tangible sensory experience in situ following a plot, author’s life, or a myth. Literary routes respond to the demand of the growing target travellers, who are more literate and active today than in the past. They are excited followers of their favourite writers, and seek ways to be in contact with them. Now it is time to rekindle the collective memory, expand the literary dimension, and offer a sensorial in situ experience by adding a literary link. For instance, myths of the Ohlone Nation based near a California wetlands use the symbolic coyote as the intermediary to teach humans how to live in harmony with their ecosystem; or in Spain, Arcipreste de Hita’s novel El Libro de Buen Amor (1330) describes traditions and gastronomy as it criss-crosses the Guadarrama mountains, alongside the Poets’ Route that includes international Nobel prize winners in literature; Don Quijote of La Mancha (1603) was first made tangible as a literary route in 1780 with a detailed topographical surveyor map inspiring visitors like Washington Irving (1829), Alexander Dumas (1861), and Hans Christian Andersen (1880) to the Spanish plains. This eventually galvanized into an innovative move to pass the Don Quijote Route Law (2007), complete with GPS coordinates. In Japan, Basho’s literary route (1700) with its natural elements changed the style of Japanese Haiku, encouraging writers around the world to follow in his footsteps, and Humboldt’s account of his Andes’ route in South America inspired Lewis & Clark, Darwin, and Muir to follow a similar path that spurred events, websites, and even a NASA astrobiology project to conserve and access the accumulated heritage of these literary routes. Economic investments in literary routes in natural settings have been initiated by worldwide government ministries of culture, recreation/tourism, environment, economy, and/or education, demonstrating commitments to the conservation of landscapes which have inspired literature. Hence, literary routes can highly contribute to cultural itineraries in natural settings. Rutas literarias inspiradas por los paisajes es un tema donde las rutas culturales y naturales se combinan para formar un valor añadido del patrimonio que es mayor que cualquiera de los dos por sí solo. El ‘Paisaje’ es, en parte, una consecuencia de las transformaciones de los seres humanos, y raramente se tiene en cuenta cómo la naturaleza ha inspirado la literatura para promover el "desarrollo intelectual de la humanidad", y por lo tanto, la transformación del patrimonio. Rutas literarias paralelas a las rutas de trashumancia abrazadas por los Sami, las Indígenas de América, o pastores españoles (llena de paisajes, marinas, y riachuelos), pueden transmitir activamente las tecnologías tradicionales, la biodiversidad, y la filosofía cósmica para la mejora de la humanidad. Por ejemplo, la profundidad de patrimonio literario inspirado en el paisaje mejora nuestra memoria colectiva a través de una red de archivos (bibliotecas, colecciones). La continua difusión de esta literatura sobrepasando lugares, barreras lingüísticas, y períodos de tiempo, ha hecho que las rutas literarias se conviertan en transmisoras de un patrimonio intangible basado en paisajes imaginarios a una experiencia sensorial tangible in situ (después de una parcela) mostrando un lugar, la vida de un autor, o un mito. Las rutas literarias responden a la demanda de las crecientes espectativas de los viajeros que, en la actualidad, son más cultos y activos que en el pasado. Son seguidores acérrimos de sus escritores favoritos, y buscan las maneras de estar en contacto con ellos. Ahora es el momento de reavivar la memoria colectiva explotando la dimensión literaria, y ofreciendo una experiencia sensorial in-situ mediante la adición de un vínculo literario. Por ejemplo, los mitos de la Nación Ohlone sede cerca de los humedales de California, utilizan simbóliocamente el coyote como intermediario para enseñar a los humanos cómo vivir en armonía con su ecosistema; o en España, la novela de del Arcipreste de Hita, El Libro de Buen Amor (1330), describe las tradiciones y la gastronomía como si se entrecruzara con la sierra de Guadarrama, junto a la Ruta de los Poetas, que incluye ganadores del Premio Nobel de Literatura. La novela Don Quijote de La Mancha (1603) se mostró como una ruta literaria de facto en 1780 con un detallado mapa topográfico, inspirando visitantes como Washington Irving (1829), Alexandre Dumas (1861), y Hans Christian Andersen (1880) a las llanuras españolas. Esto a la larga ha dado lugar a una iniciativa innovadora para aprobar la Ley de la Ruta de Don Quijote (2007), incluyendo las coordenadas GPS. En Japón, la ruta literaria de Basho ( 1700 ), con sus elementos naturales cambió el estilo de Haiku japonés, fomentando a los escritores de todo el mundo a seguir sus pasos, y el relato de Humboldt de la ruta de la Andes en América del Sur inspirado a los exploradores Lewis & Clark, Darwin, y a Muir a seguir un camino similar. Estas rutas a través del tiempo han estimulado eventos, páginas web, e incluso un proyecto de astrobiología de la NASA para la conservación y acceso del patrimonio acumulado de estas rutas literarias. Inversiones económicas en las rutas literarias en escenarios naturales han sido iniciados por los ministerios de cultura de todo el mundo, de turismo, de medio ambiente, y de economía y / o la educación, lo que demuestra compromiso con la conservación de los paisajes que han inspirado la literatura. Por lo tanto, las rutas literarias altamente pueden contribuir de forma importante a los itinerarios culturales en entornos naturales.